Evaluation of Lower Limb Muscle Synergies in Paediatric Females with and without ACL Injuries - Kemp, Laryssa (Université d'Ottawa / University of Ottawa, 2020)
Purpose: Young adolescent females are at the highest risk of sustaining an ACL injury, which may alter their movement and muscle activation patterns yet there is a lack sex- and age- specific guidelines for ACL injury management. The purpose of this study was to (1) evaluate the effects of limb dominance in a healthy uninjured population to serve as a baseline for the ACL-deficient cohort and (2) provide evidence of the neuromuscular patterns and biomechanical loading of uninjured and ACL-deficient knee joints in a female paediatric population. Methods: Eighteen active female adolescents with ACL rupture (ACLd) and 21 uninjured female adolescent controls matched for limb dominance (CON) participated in this study. Participants completed bilateral squats and drop vertical jumps (DVJ) while lower limb electromyography, kinetics and kinematics data were collected. Muscle synergies were extracted using a concatenated non-negative matrix factorization (CNMF) framework and compared between limbs, (CON dominant vs CON non-dominant and CON vs ACLd) across tasks and between limbs within tasks using intraclass correlation coefficients and statistical paramedic mapping. Results: ACLd participants took significantly longer to perform the squat relative to their uninjured peers. No significant differences were found for hip, knee and ankle peak joint flexion angles and moments between populations for the squat. Squat and DVJ muscle synergies were equivalent for dominant and non-dominant uninjured control limbs. ACL injured (ACL deficient and contralateral limbs) exhibited greater variability in DVJ synergy vectors than for the squat task. When comparing across tasks, scaling coefficients were consistently higher for the DVJ for all populations. Conclusion: Differences in lower limb kinematics, muscle activity and muscle activation patterns between dominant and non-dominant limbs indicate that limb symmetry, a clinical tool commonly used to assess rehabilitation and return to play may not provide relevant results. DVJ scaling factors were larger than those of the squat for all groups, likely due to the increased demand of that task. ACLd and CON participants completed squats and DVJ with similar lower limb joint angle patterns and muscle activity. ACL injured groups had fewer consistent vectors across tasks demonstrating greater variability in muscle activation patterns. This increased variability may be due to the ACL injury however, as injured participants were not studied pre- injury it cannot be confirmed.
Keywords: ACL Injury; Limb Dominance; Muscle Synergies; Squat; Drop Vertical Jump; Paediatric